ISSUES OF APPLICATION OF QUALITY MANAGEMENT IN THE SOCIO-ECONOMIC DEVELOPMENT OF ENTERPRISES AND ORGANIZATIONS FOR THE PURPOSES OF THE DEVELOPMENT STRATEGY OF THE REPUBLIC OF UZBEKISTAN - Maxkamov, Navruzjon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article discusses the role of quality management in the socio-economic development of enterprises and organizations, issues of ensuring the sustainability of the national economy through the application of quality management methods in production and services in the new Development Strategy of Uzbekistan for 2022-2026. The mechanisms for achieving the goals set in the Development Strategy and their role in the development of the country's economy were studied.